Screening of cellulose-degrading yeast and evaluation of its potential for degradation of coconut oil cake - Fu, Zi-huan; Liu, Jing; Zhong, Long-bin; Huang, Huan; Zhu, Peng; Wang, Cai-xing; Bai, Xin-peng (Frontiers in Microbiology, 2022)
Coconut oil cake (COC), a byproduct of oil extraction, contains high levels of cellulose. The aim of this study was to isolate a cellulose-degrading yeast from rotten dahlia that can effectively use COC as the only carbon source for cellulase secretion. Based on screening, Meyerozyma guillermondii CBS 2030 (M.guillermondii) was identified as a potential candidate, with the highest cellulolytic activity among the yeast strains isolated, with the carboxymethyl cellulase (CMCase) activity reaching 102.96 U/mL on day 5. The cellulose in COC samples was evaluated before and after degradation by M.guillermondii. Analysis based on field emission scanning electron microscopy (FESEM) revealed that the COC structure was changed significantly during the treatment, indicating effective hydrolysis. Fourier transform infrared spectroscopy (FTIR) of the modified functional groups indicated successful depolymerization of coconut cake. X-ray diffraction (XRD) and analysis of color differences established effective degradation of COC by M.guillermondii. The results demonstrate that M.guillermondii effectively secretes CMCase and degrades cellulose, which has important practical significance in COC degradation.